Clashing temporalities of care and support as key determinants of transformatory and justice potentials in urban gardens. (November 2020) - Kotsila, Panagiota; Hörschelmann, Kathrin; Anguelovski, Isabelle; Sekulova, Filka; Lazova, Yuliana
Abstract: Urban gardens, consolidating spaces as new urban commons, are faced with the contradiction and challenge of being embedded in neoliberal landscapes of urban governance. While their transformative and justice potential has often, and rightly, been celebrated –offering new pathways towards food security and sovereignty; serving social empowerment and political engagement; making cities greener, healthier and more participatory– the mechanisms that can limit such potential have not been explored as much. Focusing on community gardens that have received some municipal support, we apply a feminist political ecology lens to examine the so far under-theorized role of care and time in urban gardens, and the way these aspects are conditioning the sustenance and just distribution of benefits that we know can emerge from urban gardens. Our qualitative empirical analysis of eight municipally supported gardens in Athens, Barcelona, Dublin and Leipzig examines the conflicting timeframes and priorities that gardening projects often have to navigate, revealing how the function of urban gardens is constrained by two types of 'clashing temporalities': (i) the invisibility of gardening needs and of their social benefits in a context of limited structural support, and (ii) the undermining of care materialities in light of short municipal timeframes and fast urban growth. Highlights: Urban gardens and their transformative and justice potential depend on tangible and intangible materialities of care. The time and care work that is required for gardening benefits to accrue is invisibilised by limited structural support frameworks. Lack of long-term support for gardens jeopardises relationships and senses of community that can emerge in community gardens.